Structural Behavior of Reinforced Concrete Flat Plates Strengthened by Horizontal Reinforcement - Ameen, Ali N.; Al-Sherrawi, Mohannad H. (Engineering, Technology & Applied Science Research, 2024)
Flat plate structures consist of a slab supported directly by columns without beams or drop panels, resulting in a thinner slab with more efficient use of space. Despite these advantages, a flat plate slab is subjected to brittle punching shear. Sudden collapse may occur when a column pushes a piece of concrete from the slab above it. This paper displays Finite Element Analysis (FEA) using ABAQUS/ CAE 2019 to simulate the punching shear impact on a flat plate strengthened with horizontal steel bars of varying number and diameter, located at the compressive side of the slab. A numerical model was constructed with 8-noded hexahedral 3D brick elements for concrete and 2-noded linear 2D beam elements for steel reinforcement. The model was adapted based on experimental data. A parametric analysis was conducted to evaluate the impact of placing horizontal steel bars at the compression side of the flat plate and changing the quantity and size of these bars on the slab’s performance. The results illustrate that the shear capacity increases from 17.07% to 28.13% as the bar diameter increases and from 19.17% to 54.82% as the number of bars increases.